Pembuatan Booklet Hotel, Tempat Wisata, dan Kuliner Khas Bandung di Favehotel Hyper Square Bandung - Zalfa Dika Azahra; Sri Surjani Tjahjawati; Tangguh Dwi Pramono; Naafi Yudha Diputra (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
Bandung, as a primary tourist destination in Indonesia, offers diverse attractions including nature, culture, and distinctive local cuisine. The increasing number of visitors necessitates practical and engaging information media to assist them in planning their trips effectively. This project aimed to design a comprehensive booklet serving as a guide to Bandung's tourism and culinary delights, specifically for guests staying at Favehotel Hyper Square Bandung, which previously lacked such a dedicated digital or physical resource. Employing a Research and Development (R&D) methodology, this project adapted a development model encompassing several stages: identifying potential and problems, data collection, product design, design validation, design revision, product testing, and final revision. To assess the developed booklet's feasibility and effectiveness, an evaluation was conducted through questionnaires distributed to respondents. The data from these questionnaires were then analyzed using a quantitative descriptive analysis method, calculating the average scores for each statement. The project's findings indicate that the booklet received positive responses from respondents, with high average scores across its content, visual presentation, and ease of use. Consequently, this booklet is deemed suitable for use as an information and promotional tool for tourism within the Favehotel Hyper Square Bandung environment.